Elements Influencing College Graduate Students’ Satisfaction and Behavioral Intention to Employ MOOC in Chengdu, China - Mian, Wang (Scholar: Human Sciences, 2025)
Purpose: This article examines the factors that affect learners’ behavioral intention and satisfaction with MOOC learning in Chengdu, China. The conceptual framework is based on perceived usefulness, confirmation, learning engagement, performance expectancy, facilitating conditions, satisfaction, and behavioral intention variables. Research design, data, and methodology: A quantitative survey evaluation approach was employed throughout the inquiry. The quantitative research method was adopted in this study. 500 graduate students from the target university were selected as the sample size, and the final effective data was 462. Structural Equation Modeling (SEM) and Confirmatory Factor Analysis (CFA) were used to assess the causal relationship between the factors that were being examined. Results: According to the survey results, all six hypotheses are valid. The results show that learners’ satisfaction with MOOCs is the most important factor affecting their behavioral intention, and satisfaction, perceived usefulness, and learning engagement have more influence. Conclusions: For implication, when learners are satisfied with their learning experience with MOOCs, they will choose the MOOC platform when they need to acquire knowledge. In addition, more efforts are made in platform construction and course maintenance, enriching the interactive function design of online courses, focusing on forum maintenance, and enriching course materials.